GEO ; IMS ; (Geomatics Inventory Management System) / Nik Nur Izzatie Abdul Hadi - Abdul Hadi, Nik Nur Izzatie (2018)
This study design for the development of Geomatics – IMS (Inventory Management System) for Makmal Peralatan Ukur UiTM Arau, Perlis. İnventory management is an activity carried out to maintain the optimum number or amount of each inventory item. İn this study, the inventory refers to the land surveying instrument management. The aim of this study is to enhance the current procedure of borrowing land surveying instruments. By applying web-based Geographic Information System (GIS) and programming language we were able to manage inventory management with linkage to all database, including the database of land surveying instrument, database of time table and database of Geomatics students by using ArcGIS online to embed the map of the Surveying Instruments Laboratory and programming language; PHP, JavaScript and SQL to integrate data on the web. The target user of this system is more to geomatics students and officer. The result will make way for an effective system integrating web-based GIS. The combination of web-based GIS and land surveying, management system has many advantages which make the system more user-friendly and easy to access anytime and anywhere.